Socio-pedagogical educator and professional expertise - De Vitis, Francesca (Formazione & insegnamento, 2019)
The professional practice of the socio-pedagogical educator moves in a marshy terrain and the situations that arise, are difficult to solve with prepackaged solutions. The practice of practice and reflection on the practice, on work experience, represents a strategy to reach a clear definition of the situation that presents itself. The Iori law, has highlighted, even more the need for socio-cultural overcoming that sees the educational professions as merely welfare and custody.